2022
DOI: 10.1007/s10055-022-00633-7
|View full text |Cite
|
Sign up to set email alerts
|

“Passive or interactive virtual reality? The effectiveness for pain and anxiety reduction in pediatric patients”

Abstract: Invasive techniques such as venipuncture are painful procedures causing stress and anxiety, both in pediatric patients and in their carers. For this reason, efforts are being made to develop mitigating strategies for the patient’s pain and anxiety during the performance. To analyze and evaluate the effectiveness of the use of Virtual Reality distraction techniques as a measure of pain and anxiety reduction in pediatric patients and their parents. In addition, the effects of two modes of Virtual Reality (passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Participants in a virtual environment who did the activity showed a more significant overall gain in conceptual learning than those who did not (Roussou and Slater, 2020). Ferraz-Torres et al (2022) found that interactive virtual reality produced more significant anxiety reduction and lower pain levels than passive ones in children who underwent venipuncture. The virtual reality environment in this study was used with a controller to move to other places.…”
Section: Discussionmentioning
confidence: 92%
“…Participants in a virtual environment who did the activity showed a more significant overall gain in conceptual learning than those who did not (Roussou and Slater, 2020). Ferraz-Torres et al (2022) found that interactive virtual reality produced more significant anxiety reduction and lower pain levels than passive ones in children who underwent venipuncture. The virtual reality environment in this study was used with a controller to move to other places.…”
Section: Discussionmentioning
confidence: 92%
“…Its capacity to simulate different realities and experiences has prompted researchers to examine the potential of incorporating VR into various medical (Li et al 2017) and psychological (Maples-Keller et al 2017) interventions. VR techniques have been implemented in the treatment of phobias (Botella et al 2017), post-traumatic stress disorder (PTSD; Kothgassner et al 2019), anxiety disorders (Chan et al 2021;Rothbaum et al 2002;Parsons and Rizzo 2008;Eijlers et al 2019), depression (Falconer et al 2016), schizophrenia (Bisso et al 2020), eating disorders (Riva et al 2016a, b) and pain management (Ferraz-Torres et al 2022;Phelan et al 2021a, b;Matamala-Gomez et al 2019;Spiegel et al 2019;Vilalta-Abella et al 2015). Reducing anxiety using VR to deliver interventions has been explored and found effective through nature-based mindfulness experiences (Tarrant et al 2018;Chan et al 2021;Liszio and Masuch 2019;White et al 2018), VR distraction for pain during blood drawing (Piskorz and Czub 2018;Gerceker et al 2018;Gold and Mahrer 2018) and before entering an operating theatre (Ryu et al 2017;Arpaia et al 2022), and for cognitive behaviour therapy (CBT) and Virtual reality exposure therapy (VRET) (Baghaei et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interactivity may facilitate the immersive effects of VR, and it may also contribute to the feeling of control. 19 In this game, children have to link stars in a calm, Arctic setting. If the stars are linked properly, mythic creatures appear as a reward.…”
Section: Methodsmentioning
confidence: 99%